2006
DOI: 10.1021/es0601134
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution and Probability of Encountering Intertidal Exxon Valdez Oil on Shorelines of Three Embayments within Prince William Sound, Alaska

Abstract: We examined 32 shorelines selected at random in 2003 from shorelines in Herring Bay, Lower Pass, and Bay of Isles in Prince William Sound, Alaska, to examine the vertical distribution of oil remaining from the 1989 Exxon Valdez oil spill and to estimate the probability that sea otters and ducks would encounter oil while foraging there. On each shoreline, sampling was stratified by 1-m tide height intervals and randomly located 0.25 m2 sampling quadrats were examined for evidence of surface and subsurface oil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(159 citation statements)
references
References 21 publications
2
156
1
Order By: Relevance
“…Within PWS during the early stages of the spill, less viscous oil readily percolated into the generally finer-grained beaches (10). As the spill progressed along the GOA, the often greater porosity of more exposed beaches allowed the increasingly viscous oil to percolate into them as well (11,12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within PWS during the early stages of the spill, less viscous oil readily percolated into the generally finer-grained beaches (10). As the spill progressed along the GOA, the often greater porosity of more exposed beaches allowed the increasingly viscous oil to percolate into them as well (11,12).…”
Section: Resultsmentioning
confidence: 99%
“…The percent of oiled quadrats classified as HOR, MOR, LOR was 6, 41, and 53% in 2001, compared with 7, 20, and 73% in 2005, a change that was not statistically significant ( 2 ) 2.09, P ) 0.35, df ) 2). The apparent increases in oiled beach areas and masses between 2001 and 2005 reflect sampling error because no crude oil had been added to these beaches, and the high viscosity, high adhesion, and low concentration of the oil in these sediments preclude substantial diffusive spreading (10,21). For these reasons, we assumed that the actual proportion of beach area that is oiled, p, is constrained to decline monotonically with time.…”
Section: Methodsmentioning
confidence: 99%
“…Exxon Valdez spill, although we recognize that as long as oil remains in the environment, some individuals are likely to encounter it (Short et al, 2006). In the case of Barrow's goldeneyes, it appears that the incidence and degree of any remaining exposure was low by 2009.…”
Section: Discussionmentioning
confidence: 88%
“…Trust et al (2000) found that Barrow's goldeneyes (Bucephala islandica), a common sea duck in the area contaminated by the 1989 Exxon Valdez oil spill, had elevated EROD activity during winter 1996-97, which was interpreted as evidence of continued exposure to lingering oil. Wintering Barrow's goldeneyes in Prince William Sound inhabit nearshore areas and forage primarily on blue mussels (Mytilus trossulus) in the intertidal zone (Esler, 2000;Koehl et al, 1982;Vermeer, 1982) where much of the residual Exxon Valdez oil persisted (Short el al., 2004;Short et al, 2006).…”
Section: Measurement Of Hepatic 7-ethoxyresorufin-o-deethylase (Erod)mentioning
confidence: 99%
See 1 more Smart Citation